THE DISTRICT'S LIVABILITY OF SURAKARTA CITY - Lintang Praharyaning Suryono; Deva Fosterharoldas Swasto (Built Environment Studies, 2023)
Livability is the ability of a place to provide a comfortable and healthy atmosphere for living, doing activities, or working, which is built through urban physical order, accessibility of city services, ease of mobility, an opportunity to participate, and protection of nature so that all residents have a good quality of life. In Indonesia, the city that has the best livability value is Surakarta. However, livability in this city does not seem available to all residents because the service facilities are not evenly distributed in some areas, and many people still live in slums. Therefore, this study was structured to measure the livability of the Surakarta City area using a quantitative deductive approach. The analysis technique used is geospatial data processing and scoring. As a result, the three observed areas have fairly good livability with different scores.